2013
DOI: 10.1007/s40368-013-0012-0
|View full text |Cite
|
Sign up to set email alerts
|

Putative factors associated with molar incisor hypomineralisation: an epidemiological study

Abstract: The aetiology of MIH is not clear yet, and the results of this study support the results of previous studies regarding the putative causal effect of several factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
0
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(104 citation statements)
references
References 27 publications
1
93
0
10
Order By: Relevance
“…Several other studies found associations between specific illnesses and MIH. A number of retrospective studies found an association with higher odds of MIH and early childhood fever, including both studies that adjusted for confounding (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…Several other studies found associations between specific illnesses and MIH. A number of retrospective studies found an association with higher odds of MIH and early childhood fever, including both studies that adjusted for confounding (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the aetiology of MIH remains unclear [Alaluusua, 2010;Sönmez et al, 2013;Wuollet et al, 2014]. There are studies demonstrating a potential environmental contribution to MIH [Jan et al, 2007;Alaluusua, 2010;Souza et al, 2012;Loli et al, 2015;Oyedele et al, 2015] and other studies demonstrating evidence of the genetic influence on the occurrence of MIH [Jeremias et al, 2013b;Kühnisch et al, 2014].…”
mentioning
confidence: 99%
“…5 In fact, the enamel formation stage during which MIH arises is not currently known and there is no evidence that determines its cause. 19 With prevention as a hard-to-reach goal, the efforts of clinicians and researchers should focus on early diagnosis and restorative treatments that may remain successful over time.…”
Section: Discussionmentioning
confidence: 99%